Penerapan Inovasi Aplikasi Simda di BPKD Padang Pariaman - Cindy Fitra Rahmadani; Syamsir Syamsir; Diva Rizalia; Fani Izwar; Mivta Maharani; Nia Aprilian; S. Amanda Putri; Syakira Mishwa Hanifah (Ranah Research : Journal of Multidisciplinary Research and Development, 2023)
Analysis of the Application of SIMDA in Preparing Financial Reports at the Regional Financial Management Agency of Padang Pariaman Regency. The Financial Regional Management Implementation System (SIMDA) is an application program used to assist local governments in the field of financial management. The aim of this research is to find out how SIMDA is implemented in the Regional Financial Management Agency (BPKD) of Padang Pariaman Regency. This research is qualitative research with descriptive methods. The data in this research was collected through interviews, observation and documentation. As well as knowing employees' understanding of implementing SIMDA Finance and the obstacles faced in its implementation. There were two respondents in the study, data was collected through direct interviews with respondents. The results of the interviews and data collected were analyzed descriptively using a phenomenological approach. The research results show that employees generally understand the meaning of financial SIMDA and an overview of its implementation regarding input and output data. Obstacles faced in implementing the SIMDA Finance application: SIMDA expires quickly, the network is often offline, there is no documentation regarding summary flow diagrams showing cash flow data, the data management system is weak, procedures for viewing incidental data still take too long, office space is still limited. inadequate and the occurrence of human error